2019
DOI: 10.1016/j.scitotenv.2019.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Differential modification of the C. elegans proteome in response to acute and chronic gamma radiation: Link with reproduction decline

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Analysis of global protein expression in this study showed the modulation of proteins involved in regulating biological processes such as lipid transport, DNA replication, development of germ cells, apoptosis, transport of ions, and the development of cuticles. These results confirmed that chronic irradiation induced different molecular mechanisms than acute irradiation [71].…”
Section: Effect On Agingsupporting
confidence: 79%
See 1 more Smart Citation
“…Analysis of global protein expression in this study showed the modulation of proteins involved in regulating biological processes such as lipid transport, DNA replication, development of germ cells, apoptosis, transport of ions, and the development of cuticles. These results confirmed that chronic irradiation induced different molecular mechanisms than acute irradiation [71].…”
Section: Effect On Agingsupporting
confidence: 79%
“…This was investigated in a study by Kuzmic et al, where they show an acceleration of the aging process by exposing C. elegans to chronic irradiation. Irrespective of the dose rate and dose delivered, chronic exposure reduced the level of oxidative protein damage (carbonylation), which is a biomarker of the aging process [70]; Dubois et al also experimented with the response of C. elegans to acute and chronic exposure [71]. After chronic exposure, 168 proteins were significantly changed in the experimental group, while 369 proteins were significantly changed following acute radiation exposure.…”
Section: Effect On Agingmentioning
confidence: 99%
“…Mass spectrometry analysis were done as already described previously 66 . Briefly, peptides obtained after trypsinisation were diluted in solvent A (0.1% v/v formic acid in 2% v/v acetonitrile) and concentrated using a pre-column (C18 PepMap100, 2 cm × 100 µm I.D, 100 Å pore size, 5 µm particle size, Dionex).…”
Section: Methodsmentioning
confidence: 99%
“…Data processing was performed using MaxQuant v1.6.1.0, computing relative intensities based on label-free quantification (LFQ) with the MaxLFQ algorithm. Mass spectra and differential protein expression analysis were performed as described before using Perseus v1.6.1.3 66 . Briefly precursors ions identification was performed using the Danio rerio UniProt protein database (12 th of February 2019 with 58994 entries) supplemented with 245 proteins commonly found as contaminants and a false positive rate of 1% for protein identification.…”
Section: Methodsmentioning
confidence: 99%
“…The Chernobyl nuclear accident on April 26 th 1986 was responsible for a large-scale release of radionuclides into the surrounding ecosystem, resulting in long-term exposure of the local and wider environment. Exposure to radioactivity in controlled, high dose laboratory studies has been shown to have effects on soil invertebrate species including earthworms (Hertel-Aas et al, 2007;Rusin et al, 2019;Sowmithra et al, 2015), springtails (Nakamori et al, 2008) and nematodes (Dubois et al, 2019;Lecomte-Pradines et al, 2017). Further, research on the long-term effects of ionising radiation in the surrounds of the former power station, now known as the Chernobyl Exclusion Zone or CEZ, have provided information on the physiological and ecological responses of individuals, populations and ecosystems to chronic radiation exposure (see Beresford et al, 2016;Geras'kin et al, 2008;Hinton et al, 2007;Lourenco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%